2020
DOI: 10.1111/eth.13009
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise differentially impacts call types in a Japanese treefrog (Buergeria japonica)

Abstract: Acoustic noise from automobile traffic impedes communication between signaling animals. To overcome the acoustic interference imposed by anthropogenic noise, species across taxa adjust their signaling behavior to increase signal saliency. As most of the spectral energy of anthropogenic noise is concentrated at low acoustic frequencies, species with lower frequency signals are expected to be more affected. Thus, species with low‐frequency signals are under stronger pressure to adjust their signaling behaviors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…My observation showed that B. otai used a combination of visual and vocal cues in a competition for signaling site and that long calls used in the competition were distinct from normal advertisement calls (Legett et al, 2020a; Wang et al, 2017). If Buergeria otai alters the call types to coordinate with different behaviors warrants further examination (Legett et al, 2020b).…”
Section: Figurementioning
confidence: 99%
“…My observation showed that B. otai used a combination of visual and vocal cues in a competition for signaling site and that long calls used in the competition were distinct from normal advertisement calls (Legett et al, 2020a; Wang et al, 2017). If Buergeria otai alters the call types to coordinate with different behaviors warrants further examination (Legett et al, 2020b).…”
Section: Figurementioning
confidence: 99%
“…Most male anurans produce advertisement calls to attract mates and defend territories (Gerhardt, 1994 ; Lee et al., 2023 ) but traffic noise overlaps many species' frequency niches and has high amplitude (Bee & Swanson, 2007 ; Cunnington & Fahrig, 2010 ; Grace & Noss, 2018 ), which can mask anuran vocalizations (Bee & Swanson, 2007 ; Lee et al., 2023 ). To compensate for traffic noise, some species increase the dominant frequency (Caorsi et al., 2017 ; Grenat et al., 2019 ; Leon et al., 2019 ), amplitude (Halfwerk et al., 2016 ; Leon et al., 2019 ), call rate (Cunnington & Fahrig, 2010 ; Grenat et al., 2019 ; Legett et al., 2020 ), or number of notes (Grace & Noss, 2018 ; Leon et al., 2019 ) of their vocalizations, whereas others avoid calling during periods of high background noise (Vargas‐Salinas & Amézquita, 2013 ). Though these strategies can improve vocalization audibility, changing call characteristics can be energetically costly, constrained by physiology, and can increase predation risk (Gerhardt, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the strategies used by anurans to reduce or avoid the overlap between biotic and anthropic noises on their calls, there are changes in amplitude (Halfwerk et al, 2016;Parris et al, 2009;Yi & Sheridan, 2019), frequency (Caorsi et al, 2017;Cunnington & Fahrig, 2010), duration (Zhao et al, 2021) and emission rate (Hanna et al, 2014;Kaiser & Hammers, 2009;Legett et al, 2020). These changes can be advantageous when the individuals are under external influences, since the acoustic signals indicate physical condition of the individuals.…”
Section: Introductionmentioning
confidence: 99%